Impact of Severe Hypoxia on the Metabolic Alterations in the Fresh Water Catfish Clarias batrachus - Kumar, Karthik (International Journal of Pharmaceutical & Biological Archive, 2012)
Impact of Severe Hypoxia on the Metabolic Alterations in the Fresh Water Catfish Clarias batrachus